Pengembangan Model Community-Based Tourism (Cbt) Pada Masayarakat Di Desa Bongkudai Baru Kabupaten Bolaang Mongondow Timur, Sulawesi Utara Metode: Soft Sytem Methodology (Ssm) - Purnomo, Dwi; Djunaedi, Achmad (Jurnal Ilmiah Pariwisata; Vol 24 No 1 (2019): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v24i1.1243, 2019)
This study aims to formulate models in terms develop Bongkudai Baru Village by the concept of Community-Based Tourism (CBT). Soft System Methodology (SSM) is used to complete these neccesity. Definitively, SSM can be interpreted as a process to find out what is most important from everyday real life; SSM users do learning that starts from identifying to achieving and optimizing the function of this problem (Checkland and Poulter, 2006 in Sudarsono, 2012). This is qualitative research, with observation, in depth interview and Focus Group Discussion (FGD) to obtain primary data. Meanwhile, secondary data obtained through a literature study of sources that have relevance  to  the  focus  of  the  study.  The  results  of  the  study  revealed  that  the development model is based on activities carried out by the local community with the SSM method, namely: a) understanding and identifying potentials and resources availability; b) enhance community awareness in engaging directly and collaborating towards development process; c) create local institutional instruments; d) formulating actions, implementation, management and control; e) formulate operational regulations and procedures for the implementation of tourism activities; and f) Building and developing   businesses   in   the   tourism   sector   to   increase   equal   benefits   and comprehensive manner .